THE CONCEPT OF AN ENTITY IN AN EFFORT TO SUPPORT INTERNAL CONTROL IN MSME KUNCI SOROT IN JEMBER - Pramono, Olivia Falen; Kusuma, Dedy Wijaya; Ilmi, Mainatul (Journal of Applied Finance and Accounting, 2023)
MSME Kunci Sorot is engaged in the film industry in Jember. The business he owns is leasing equipment needed for shooting and filmmaking. MSME Kunci Sorot are also MSMEs that have large assets by MSME standards. This causes internal control to be needed to maintain the assets owned. The research objectives are (1) an analysis of the implementation of the entity concept in the MSME Kunci Sorot and (2) an analysis of internal control in the MSME Kunci Sorot. The research method used is descriptive qualitative and uses a case study approach. The sampling technique used snowball sampling. The result of this research is that MSME Kunci Sorot still needs to fully implement the entity concept. The entity concept applied in the MSME Kunci Sorot is still very simple to record. The entity concept that has not been implemented optimally causes the applied internal control to have many weaknesses. The results of the study indicate that internal control is needed in maintaining assets owned and facilitating daily operational processes. MSMEs that tend to be simple still need internal control so that operational processes are efficient and effective.